Getting the Most from Working with Higher Education: A review of methods used within a participatory design activity involving KS3 special school pupils and undergraduate and post-graduate industrial design students - Torrens, George Edward; Newton, Helen (Design and Technology Education: An International Journal, 2013)
This paper provides education-based researchers and practitioners with the preferred research and design methods used by Higher Education Institute (HEI) students and Key Stage 3 (KS3) pupils applied within a participatory approach to a design activity. The outcomes were that both pupils and students found informal (unstructured) interview to be effective in creating dialogue alongside meeting in person. Students commented on the friendly environment created by staff within which the pupils felt safe to express themselves. They found the co-design activity in some cases difficult due to communication issues. Recommendations are that the HEI students would benefit from a thorough literature review of the medical conditions associated with the pupils and their school activities; an initial informal meeting or group activity involving students and pupils would reduce shyness and perform an icebreaking role prior to the initial interview; the use of drawing templates or low resolution sketch models for pupils to draw on or handle and modify to help define a product specification; and, role playing alongside other visual prompts that enable the pupils to visualise the function of the student-proposed designs. Pupils benefited through seeing professional techniques of visual communication and design practices being applied during the collaboration.